2002
DOI: 10.1126/science.1064987
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Computational Strategy to Define Protein Interaction Networks for Peptide Recognition Modules

Abstract: Peptide recognition modules mediate many protein-protein interactions critical for the assembly of macromolecular complexes. Complete genome sequences have revealed thousands of these domains, requiring improved methods for identifying their physiologically relevant binding partners. We have developed a strategy combining computational prediction of interactions from phage-display ligand consensus sequences with large-scale two-hybrid physical interaction tests. Application to yeast SH3 domains generated a pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
468
0
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(493 citation statements)
references
References 20 publications
12
468
0
8
Order By: Relevance
“…Largescale proteomic studies have also demonstrated interactions between Las17 and Ysc84, including isolation in complexes from cells (Gavin et al, 2002;Tong et al, 2002;Landgraf et al, 2004;Tarassov et al, 2008). However, to date, no role has been shown for Ysc84 in endocytosis.…”
Section: Function Of Ysc84 In Endocytosismentioning
confidence: 99%
“…Largescale proteomic studies have also demonstrated interactions between Las17 and Ysc84, including isolation in complexes from cells (Gavin et al, 2002;Tong et al, 2002;Landgraf et al, 2004;Tarassov et al, 2008). However, to date, no role has been shown for Ysc84 in endocytosis.…”
Section: Function Of Ysc84 In Endocytosismentioning
confidence: 99%
“…A consensus sequence PxxxPPxxP has been reported as the ligand for the type I myosin SH3 domains, and a single predicted ligand is present within the last 12 residues of the PRD of Pan1 (Tong et al, 2002). To test whether this Cterminal ligand is important for the interaction between Pan1 and the myosins, we made a truncated construct, His 6 -Pan1 PRD⌬12 (aa1310 -1468), in which the last 12 amino acids were removed.…”
Section: The Pan1 Prd Directly Interacts With the Sh3 Domains Of The mentioning
confidence: 99%
“…Confidence yeast two-hybrid [32][33][34][35] or affinity purification of complexes 36,37 ) data sets and obtain a tolerably accurate view of the total possible network of interactions that might occur between cellular proteins. Links seen in multiple data sets (even if each of these is very noisy) reinforce and greatly improve the quality of the network; thus, even links observed in weak or noisy data sets are of value as they may sum with other such links to form statistically significant informational interactions.…”
Section: Low High Mediummentioning
confidence: 99%